Kajian Literatur Analisis Faktor Perilaku PUS tentang Penapisan Kanker Serviks dengan Metode IVA - Wahyuni, Ida Tri; Wahyuni, Sri; Astuti, Endri (JURNAL KEBIDANAN, 2025)
World Health Organization (WHO) states, there are an estimated 500,000 people with cervical cancer every year in the world and 274,000 or 54.8% of deaths occur every year due to this preventable disease. The prevalence of non-communicable diseases in Riskesdas in 2018 shows an increase, among others in the incidence of cancer which has increased from 1.4% to 1.8%. Cervical cancer is the second most deadly disease contributor in women after breast cancer. The purpose of the study was to analyze the results of the literature review by researching factors related to couples of childbearing age behavior in screening for cervical cancer by the VIA method.This type of qualitative research uses library research. The design used was literature review, articles were collected using search engines such as Google Scholar, Science Direct, EBSCO, Proquest, and Repository Poltekkes Kemenkes Seamarang. Criteria for articles used are those published in 2015-2020. Based on 12 the articles collected, the results show that there is a significant relationship between knowledge, access to information / mass media and husband's support with couples of childbearing behavior in screening for cervical cancer by VIA method, and there is no relationship between education with couples of childbearing behavior in screening for cervical cancer with VIA method. The role of midwives with health cadres and husbands is very influential on the behavior of couples of childbearing women in screening for cervical cancer by the VIA method. Keywords : Behavior, Couples of Childbearing , Cervical Cancer, VIA